The combined absence of the transcription factors Rel and RelA leads to multiple hemopoietic cell defects - Grossmann, Mathis (The National Academy of Sciences, 1999)
Individual Rel/NF-κB transcription factors, although dispensable for the development and maturation of most hemopoietic cells, are critical regulators of normal immune function. Redundancy among these proteins prompted us to examine the role of Rel and RelA in hemopoiesis by using mice that lack both subunits. Because of the death of double-mutant fetuses at day 13.5 of gestation (E13.5), E12 fetal liver hemopoietic progenitors were used for in vitro cultures and for repopulating stem cell studies in lethally irradiated normal recipient mice. Most striking, Rel/RelA-deficient hemopoietic precursors failed to promote the survival of myeloablated mice. This phenotype was associated with several defects including a reduction of spleen colony-forming unit progenitors, impaired erythropoiesis, and a deregulated expansion of granulocytes. In vitro progenitor assays also revealed that Rel or RelA serves an antiapoptotic role during monocyte differentiation. Despite the combined loss of Rel and RelA leading to these hemopoietic defects, c-rel(−/−)rela(−/−) stem cells contributed to the development of all lineages in mice engrafted with double-mutant fetal liver cells and normal bone marrow cells, albeit in a reduced fashion compared with controls. Collectively, these data indicate the loss of Rel and RelA does not appear to affect pluripotent stem cells; rather, Rel and RelA serve redundant functions in regulating differentiation and survival of committed progenitors in multiple hemopoietic lineages.